Analyzing The Effect of Family Support, Friend Support, Coworker Support, and Self-Efficacy on Employee Resilience: An Empirical Analysis - M S KishanVarma, K Kalpana (Journal of Informatics Education and Research, 2024)
This study investigates the interplay between family support, friend support, coworker support, self-efficacy, and resilience in the workplace, with a specific focus on gender as a moderating variable. Through a cross-sectional survey design with 300 participants, the findings reveal that friend support and self-efficacy significantly predict resilience among employees, emphasizing the critical roles of personal relationships and individual beliefs. While gender exhibits a marginal effect on resilience, the study does not find significant moderation effects, suggesting that the relationships between key variables and resilience are consistent across different gender groups. The results underscore the universal importance of social support and self-efficacy in fostering employee resilience, providing valuable insights for organizational strategies aimed at enhancing employee well-being. Future research is encouraged to explore longitudinal dynamics, qualitative perspectives, and the intersectionality of various demographic factors in shaping workplace resilience.